Religious Nationalism of Kèaè Pesantren: K.H. Zainal Arifin Together with Oreng Kenek Builds Nationality and Curbs Colonialism in Sumenep - Iskamar; Abd A'la; Damanhuri (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The spread of Islam brought by K.H. Zainal Arifin, one of Syaikhona Kholil Bangkalan's students who born in Sumenep, has a unique scheme because it intersects with Islamic preaching on the one hand, and fighting colonialism on the other. This article aims to describe the religious nationalism of K.H. Zainal Arifin was recorded in his movement defending the interests of "oreng kenek"(common people). This research located in Sumenep, East Java, focusing K.H. Zainal Arifin as research subjects which a local figure of Sarekat Islam and Nahdlatul Ulama. The method of research is qualitative with a historical approach. The finding explain that the nationalism of K.H. Zainal Arifin's religious nationalism originates from his interpretation of Islamic teachings. The first one, K.H. Zainal Arifin founded the Islamic Boarding School in Terate to combat illiteracy which befell the "oreng kene’" because they couldn’t study in schools founded by the Colonial Government. The second one, K.H. Zainal Arifin mobilized followers of the Naqshbandiyah order and Laskar Sabilillah to support Sarekat Islam's struggle to break the colonial hegemony. As a result, K.H. Zainal Arifin not only succeeded in activating strong ulama-santri (teacher-student) resistance nodes in stemming colonialism but also made Islam accepted by the local community peacefully. K.H. Zainal Arifin’s legacy is strong evidence of how religious leaders in a pesantren (Islamic boarding) practice religious nationalism.